Validation of IgY for the diagnosis of Streptococcus agalactiae-caused endocarditis and bacterial meningitis in Nile tilapia (Oreochromis niloticus) - Eto, Silas F. [UNESP] (2018)
Streptococcus agalactiae (Sta), which belongs to Lancefield group B, causes sepsis, endocarditis and bacterial meningitis in human neonates and Nile tilapia. Because the pathophysiology of Sta infection is partially similar in both species, the identification of biomarkers for the diagnosis and study of this disease is of importance for human and animal health. Therefore, in the present study, we produced an immunoglobulin Y (IgY) by immunizing laying hens with Sta proteins and evaluated its ability to detect Sta in paraffinized tilapia brain and cardiac tissue by direct immunofluorescence (IMF) and indirect immunohistochemistry (IHC). The IgY produced was effective in the diagnosis of Sta infection in Nile tilapia, justifying the use of this species as a biomodel for the study of this disease.